Touching at Depth During the COVID-19 Pandemic: What Not Touching Babies Can Teach Us about How to Improve Healthcare - Rice, Kathleen (Ars Medica, 2023)
After maybe three days, my husband’s parents came over from Salt Spring Island. We made a mug of coffee, we got muffins, and they brought their own lawn chairs. They sat out on the lawn below our apartment balcony and looked up at their grandson, our baby, and I just bawled the whole time.